Analysis of Readiness Factors for Islamic Boarding Schools to Implement the Merdeka Curriculum - Salman Alparis Sormin; Yonarlianto Tembang; Lay Riwu (Technium Social Sciences Journal, 2023)
The curriculum is the main key in the process of implementing learning activities that take place dynamically. The main innovation in the world of education in Indonesia is the implementation of an independent curriculum and an independent learning curriculum program that is based on a constructivist approach and an inquiry-based learning process. The purpose of the research conducted was to analyze the factors that influence the readiness of Santri Perbatasan Timur Islamic Boarding School in implementing the Merdeka curriculum in an integrative manner.Data collection was carried out through structured interviews conducted with teachers, principals, students on the process of planning, implementing, and evaluating or reflecting on each component element and process of implementing the curriculum and the process of direct observation at the Santri Perbatasan Timur Islamic boarding school. The data collected is in the form of quantitative data and qualitative data which is then carried out by triangulation of data from each source of primary data and secondary data so that it can be processed into complete information. Primary data is in the form of interview results as evidenced by evidence of transcripts related to the implementation of the Merdeka learning curriculum and aspects of its development.